Brain MR Imaging in Neonatal Hyperammonemic Encephalopathy Resulting from Proximal Urea Cycle Disorders - Takanashi, Jun-ichi (AJNR Am J Neuroradiol, 2003)
Summary: We present brain MR images in three patients with neonatal-onset hyperammonemic encephalopathy resulting from urea-cycle disorders (two sisters with deficiency of the carbamyl phosphate synthetase I reaction step and one boy with an ornithine transcarbamylase deficiency). MR imaging revealed almost identical findings of injury to the bilateral lentiform nuclei and the deep sulci of the insular and perirolandic regions; to our knowledge, this pattern has not been previously reported. We hypothesize that these lesions presumably reflect the distribution of brain injury due to hypoperfusion secondary to hyperammonemia and hyperglutaminemia in the neonatal period.